Developing a Smoking Cessation Intervention for People With Severe Mental Illness Treated by Flexible Assertive Community Treatment Teams in the Netherlands: A Delphi Study - Küçükaksu, Müge H.; Hoekstra, Trynke; Jansen, Lola; Vermeulen, Jentien; Adriaanse, Marcel C.; van Meijel, Berno (Frontiers in Psychiatry, 2022)
Background: There is still limited evidence on the effectiveness and implementation of smoking cessation interventions for people with severe mental illness (SMI) in Dutch outpatient psychiatric settings. The present study aimed to establish expert consensus on the core components and strategies to optimise practical implementation of a smoking cessation intervention for people treated by Flexible Assertive Community Treatment (FACT) teams in the Netherlands. Design: A modified Delphi method was applied to reach consensus on three core components (behavioural counselling, pharmacological treatment and peer support) of the intervention. The Delphi panel comprised five experts with different professional backgrounds. We proposed a first intervention concept. The panel critically examined the evolving concept in three iterative rounds of 90 minutes each. Responses were recorded, transcribed verbatim and thematically analysed. Results: Overall, results yielded that behavioural counselling should focus on preparation for smoking cessation, guidance, relapse prevention and normalisation. Pharmacological treatment consisting of nicotine replacement therapy (NRT), Varenicline or Bupropion, under supervision of a psychiatrist, was recommended. The panel agreed on integrating peer support as a regular part of the intervention, thus fostering emotional and practical support among patients. Treatment of a co-morbid cannabis use disorder needs to be integrated into the intervention if indicated. Regarding implementation, staff’s motivation to support smoking cessation was considered essential. For each ambulatory team, two mental health care professionals will have a central role in delivering the intervention. Conclusions: This study provides insight into expert consensus on the core components of a smoking cessation intervention for people with SMI. The results of this study were used for the development of a comprehensive smoking cessation program.